THE NATURE AND ESSENCE OF HUMAN IN THE QUR'AN - Abdelaziz Abbaci (Sadra International Institute, 2024)
This article discusses various concepts and views on defining the human being in the context of achieving perfection. These concepts include perspectives from various disciplines and intellectual traditions, such as philosophy, Sufism, psychology, and religion. From a philosophical standpoint, the ideal human is seen as an individual who achieves wisdom both theoretically and practically, by mastering their instincts and potentials. Sufism, on the other hand, emphasizes that human perfection lies in love and one's relationship with God. On another note, the concept of strength and weakness is addressed, where some views suggest that strength is the key to perfection, while others believe that perfection lies in self-awareness and love for others. From a religious perspective, human perfection can be achieved through a deep understanding of the self and a proper relationship with God. This means that this research highlights the importance of understanding the self as a first step in the journey towards true perfection, which ultimately is the awareness of absolute dependence on God.